Superabsorbent cryogels decorated with silver nanoparticles as a novel technology for emergency point-of-use water treatment - Loo, Siew Leng (2016)
Providing potable water to the affected population (AP) is one of the first priorities after a disaster. However, the process in providing potable water to the AP is often constrained by the absence of an adequate power supply and limited means of transportation. As such, compact and easily-deployable emergency water technologies with simple and relatively low-energy operation are desirable. The aim of this research was to develop a novel infrastructure-independent approach for point-of-use water treatment through the fabrication of cryogels. Macroporous cryogels, which are formed by conducting a polymerization reaction in a semifrozen system in which the ice crystals (for aqueous systems) act as the porogens, display exceptional mechanical and swelling properties. These cryogels were further functionalized with silver nanoparticles to impart antimicrobial properties. Inspired by the remarkable mechanical and swelling-deswelling properties of cryogels, a novel approach was proposed in which the cryogels can be used as a sorbent to treat water. The method developed in this research offers the simplicity of allowing the cryogel to swell in contaminated water after which the treated water can be recovered by a simple squeezing step. By using the proposed approach, the cryogels are envisioned to remove particulates via size exclusion, and inactivate bacteria through the action of AgNPs.